KERJASAMA EKONOMI INDONESIA-SINGAPURA DALAM REALISASI SPECIAL ECONOMIC ZONE (SEZ) DI BATAM, BINTAN DAN KARIMUN - Arjuna, Desy; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research discusses about the realization of economic cooperation between Indonesia and Singapore on Special Economic Zone in the islands of Batam, Bintan, and Karimun. Batam is a region that established to be an investment destination area, including foreign investment and domestic investment by the government. It is supported by the strategic location of Batam, which is located near Malaysia and Singapore that makes Batam a profitable place for investment. The development of special economic zones is one of Indonesia’s strategies to increase direct investment in the country.Under qualitative approach, this research uses inductive analysis method that can find the fact and problem solver based on the research data which is collected from books, journals, articles, mass media, internet, and website related to the research, etc. The research locations are in the Islands of Batam, Bintan and Karimun of Riau Islands.The result of this research shows the existence of the realization from economic cooperation between Indonesia and Singapore on special economic zone, including: the signing of framework agreement for economic cooperation in the vary sectors such as investment, and free trade and free port zone establishment. The realization of Singapore’s investment in Indonesia from 2010 to the first quarter of 2015 was US$28.35 billion dollar. In 2015, the realization of Singapore’s investment reach US$2.5 billion dollar. In the trade sector, Indonesia and Singapore established Joint Investment Promotion to promote Batam, Bintan and Karimun to the countries in East Asia. In the labors sector, the two governments organized a Tripartite Workshop on Manpower Management, and collaborated to increase the competitiveness of the caregiver and nurse from Indonesia.Key word: realization, economic cooperation, region, special economic zone.